PERANCANGAN SISTEM INFORMASI PERSEDIAAN OBAT BERBASIS WEB PADA APOTEK BANTARJAYA BEKASI - Rahmanita, Annisa; Suryani, Nining; Priyanti, Evy (JUTIM (Jurnal Teknik Informatika Musirawas), 2022)
Based on the results of researchers' observations of the Bantarjaya Pharmacy, especially the drug procurement system, this research was carried out. The drug procurement process at the Bantarjaya Pharmacy is currently out of control and faces various challenges. Among them, there are often inconsistencies between recorded drug data and drugs that are actually available, and reports are still made manually, so that data recording becomes incorrect and ineffective. Expired but not easily identifiable drugs is another problem that often arises. The researcher came to the conclusion that the Bantarjaya Pharmacy needed a good drug supply system to make it easier for officers to collect drug data, both incoming and outgoing, as well as for stock verification. The waterfall method, data collection techniques, observations, interviews, and literature studies are used in the design of this drug supply information system. The design of a computerized drug supply information system can be an ideal way to overcome the problems that exist at the Bantarjaya Pharmacy which used to still use a manual approach. Because Bantarjaya Pharmacy can operate more effectively and efficiently if there is a computerized system.